HDAC3 inhibition improves urinary‐concentrating defect in hypokalaemia by promoting AQP2 transcription. (25th February 2022) - Xu, Long; Xie, Haixia; Hu, Shan; Zhao, Xiaoduo; Han, Mengke; Liu, Qiaojuan; Feng, Pinning; Wang, Weidong; Li, Chunling
Abstract: Aim: This study investigated whether enhanced histone acetylation, achieved by inhibiting histone deacetylases (HDACs), could prevent decreased aquaporin‐2 (AQP2) expression during hypokalaemia. Methods: Male Wistar rats were fed a potassium‐free diet with or without 4‐phenylbutyric acid (4‐PBA) or the selective HDAC3 inhibitor RGFP966 for 4 days. Primary renal inner medullary collecting duct (IMCD) cells and immortalized mouse cortical collecting duct (mpkCCD) cells were cultured in potassium‐deprivation medium with or without HDAC inhibitors. Results: 4‐PBA increased the levels of AQP2 mRNA and protein in the kidney inner medullae in hypokalaemic (HK) rats, which was associated with decreased urine output and increased urinary osmolality. The level of acetylated H3K27 (H3K27ac) protein was decreased in the inner medullae of HK rat kidneys; this decrease was mitigated by 4‐PBA. The H3K27ac levels were decreased in IMCD and mpkCCD cells cultured in potassium‐deprivation medium. Decreased H3K27ac in the Aqp2 promoter region was associated with reduced Aqp2 mRNA levels. HDAC3 protein expression was upregulated in mpkCCD and IMCD cells in response to potassium deprivation, and the binding of HDAC3 to the Aqp2 promoter was also increased. RGFP966 increased the levels of H3K27ac and AQP2 proteins and enhanced binding between H3K27ac and AQP2 in mpkCCD cells. Furthermore, RGFP966 reversed the hypokalaemia‐induced downregulation of AQP2 and H3K27ac and alleviated polyuria in rats. RGFP966 increased interstitial osmolality in the kidney inner medullae of HK rats but did not affect urinary cAMP levels. Conclusion: HDAC inhibitors prevented the downregulation of AQP2 induced by potassium deprivation, probably by enhancing H3K27 acetylation.